Deal with budget impacts on campus safety. Issue 12 (12th March 2020) - Miles, David
Abstract : Having worked at a private university for most of my career in public safety, I can tell you from experience that one of the biggest issues we face is our budget. I am confident that all my colleagues from other universities, including state‐funded schools, have at some time had to deal with budget reductions.